Smart Factories in the Age of Industry 4.0 - Grabowska Sandra (Management Systems in Production Engineering, 2020)
Over the last few years, the Industry 4.0 concept (called the Fourth Industrial Revolution) has attracted attention among both academics and practitioners. Industry 4.0 is a very broad domain including production processes, efficiency, data management, relationship with consumers, competitiveness, and much more. Therefore, the aim of the paper is to present new factory archetypes. The manuscript uses a synthesis of literature (scientific studies and industrial reports). Based on the results obtained, the archetypes of factories of Industry 4.0 are described. The presented manuscript contributes to the development of literature on the concept of Industry 4.0. The results obtained from the analysis of the literature not only summarize the existing knowledge about Smart Factories, but also indicate the directions of potential research.